Modeling Techniques with Positive Reinforcement in Improving Personal Hygiene Behavior among People with Intellectual Disabilities at the Wirajaya Center in Makassar - Mubarak, Muhammad Fahmi; Mildawati, Milly; Yuliani, Dwi (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
People with intellectual disabilities often have difficulty maintaining personal hygiene due to their limited intellectual functioning. Modeling techniques are often less effective due to the lack of subsequent reinforcement. To assess how effective modeling techniques combined with positive reinforcement are in helping people with intellectual disabilities at Sentra Wirajaya Makassar to better maintain personal hygiene. This study used a quantitative method with a single subject design (Single Subject Design/SSD) type A-B-A. Data were collected by observing the subjects personal hygiene behavior before, during, and after the intervention. After implementing this technique, there was a clear improvement in personal hygiene behavior in people with intellectual disabilities. This is seen from the improving trend graph, positive changes in behavioral levels, and more stable behavior. The analysis shows that this intervention has a strong positive impact. Modeling techniques combined with positive reinforcement are very effective in improving personal hygiene in people with intellectual disabilities. Social workers are advised to use this approach to help address personal hygiene issues in this group effectively.